2010
DOI: 10.4012/dmj.2009-099
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment of tribochemical treatment and phosphoric acid ester monomer of zirconia ceramics enhances the bonding durability of resin-based luting cements

Abstract: The aim of the present study was to evaluate the bonding durability of resin-based luting cement to partially stabilized tetragonal zirconia (Y-TZP) achieved by combination treatment of tribochemical (TBC) treatment and two different phosphate acid ester monomers. Two phosphate acid ester monomers (EP: Epricord opaque primer, AZ: AZ primer) were applied to each surface modification followed by application of resin-based luting cement (Rely-X ARC). Bonding specimens were placed in deionized water at 37°C and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 32 publications
3
54
1
2
Order By: Relevance
“…We have previously reported that with an optimal combination of primer conditioning and surface modification treatments, a maximum bond strength of 49.4 MPa was achieved between zirconia and resin cement 20) . In another study, we reported that the bond strength of resin cement to CAD/CAM ceramic was improved by a combined application of tribochemical system and metal primer on the bonding surface 21) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously reported that with an optimal combination of primer conditioning and surface modification treatments, a maximum bond strength of 49.4 MPa was achieved between zirconia and resin cement 20) . In another study, we reported that the bond strength of resin cement to CAD/CAM ceramic was improved by a combined application of tribochemical system and metal primer on the bonding surface 21) .…”
Section: Discussionmentioning
confidence: 99%
“…In light of the favorable results obtained in our previous studies 20,21) , we decided to challenge the conventional porcelain layering technique. A novel fabrication method based on the tested adhesion technique 21) was proposed for all-ceramic restorations, whereby CAD/CAM fabricated veneering ceramics would be bonded to zirconia frameworks using resin cements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different surface treatments, involving primers and silane coupling agents, are available and reported to enhance the bonding strength of resin cement to porcelain and zirconia [10][11][12][13] . These surface modi cation methods include acid etching, sandblasting, tribochemical treatment, and the application of phosphoric acid monomer [14][15][16][17] . In particular, acid etching using hydro uoric acid solution has been recommended to enhance the surface bonding characteristics of LDCs 18 19 .…”
Section: Introductionmentioning
confidence: 99%